CULTIVATION OF LUDWIGIA PERUVIANA IN SOIL WITH HIGH LEVELS OF NICKEL - Pereira, Cristiano De Aguiar; Schneider, Giovana; Hofstätter, Mathias; Borges, Amanda Pastório; Weber, Ani Carolina; Willrich, Joana Elisa; da Silva, Bruno Eduardo; Henn, Guilherme Schwingel Henn; de Freitas, Elisete Maria; Hoehne, Lucélia (Editora Impacto Científico, 2025)
This study evaluated the cultivation of Ludwigia peruviana in soil contaminated with nickel (Ni), a heavy metal (HM) micronutrient that is toxic in high concentrations. Excess nickel poses risk to both human health and the environment. Five conditions were evaluated using different proportions of contaminated soil and substrate (0:100, 25:75, 50:50, 75:25, and 100:0), with ten replicates per treatment and one plant per pot. The cultivation period lasted 14 weeks in a greenhouse under controlled temperature and humidity conditions. Throughout the experiments, plant growth and chlorophyll content were monitored weekly, while flower production was recorded daily. At the end of the experiment, root length, total dry mass, and metal concentrations in different plant tissues were analyzed. Results indicated that L. peruviana exhibited low Ni uptake, accumulating only small amounts in the roots under lower Ni contamination levels. Additionally, exposure to excess Ni negatively affected plant growth, sprouting, chlorophyll content, total dry mass, root length, and reproductive development. These findings suggest that L. peruviana is not suitable for the phytoremediation of Ni-contaminated areas. However, due to its ability to thrive in compacted and nutrient-poor soils, this species may still be valuable as a bioindicator and for revegetation programs in degraded areas. DOI: https://doi.org/10.56238/edimpacto2025.080-010